PENGARUH PEMENUHAN PERUMAHAN DINAS PRAJURIT TERHADAP KESIAPSIAGAAN OPERASIONAL BRIGIF 4 MARINIR/BS - Putu Dwi Amir Syarifudin; Fadelan Fadelan; Ary Kurniawan (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The Brigade Infantry 4 Marines is one of the Marine Corps executing Commands which is under the command of the Marine Corps Headquarter. The main task of this unit is to foster and prepare the strength and capability of the combat elements in its lower ranks to always have high preparedness in carrying out amphibious operations and other operational tasks. In carrying out its main tasks, operational preparedness is one of many important things for 4th Marines Infantry Brigade, one of the supporting factor for operational preparedness is the fulfillment of housing needs for soldiers. The operational readiness of a unit can be seen through the speed and completeness in the activities of gathering and deploying troops along with all the equipment or materials needed to carry out tasks, which are carried out to anticipate in dealing with various threats and situations that occur in society, both war or disaster conditions. Its deployment requires organization and through appropriate and efficient steps so that it is hoped that its speed can be projected throughout the territory of the Unitary State of the Republic of Indonesia. The purpose of this study was to see the effect of the fulfillment of official housing and the zoning of soldiers' residences on the operational preparedness of the 4th Marines Infantry Brigade. This study uses quantitative methods with data processing using SPSS. The sample used in this study is based on the Slovin formula as many as 300 people. The results in this study indicate that there is a positive and significant effect between the fulfillment of official housing on the operational readiness of soldiers with at value of 33,257. there is a positive and significant effect between the zoning of the residence on the operational preparedness of soldiers with t value of 6,559, and a simultaneous effect with f value of 919,936. The coefficient of determination of the relationship between the Service Housing Fulfillment and Regionalization Tests on Soldier Operational Preparedness is strong at 93.2%. The results of the SPSS calculation obtained a value of R2 = 0.868, which means that 86.8% of Soldier Operational Preparedness can be explained by the Service Housing Fulfillment variable while the remaining 13.2% is influenced by other variables outside the model studied